The journalist cases in Istanbul and eastern independence tribunals according to the reports of American diplomats - Bedir, Ayşe (Afyon Kocatepe Üniversitesi)
The abolition of the sultanate but the caliphate was left behind for a while after the War of Turkish Independence, the dissolution of the Parliament itself, the renewal of the elections, the establishment of the People's Party, the declaration of the Republic caused the reaction of the Istanbul press. These developments led to the establishment of İstiklâl Mahkemeleri (the Independence Tribunals) in Istanbul. Moreover, on 4 March 1925, with the decision of the Assembly, the Eastern Independence Tribunal was established to suppress the Sheikh Said Rebellion. In the trial process, Sheikh Said claimed that some of the newspaper publications had dragged them to the rebellion and that had been effective in their being against the government. These developments led to the establishment of the Independence Tribunals in Istanbul and El-Aziz. The trials which are known as the Gazeteciler Davası (the Journalist Cases) and the developments on the subject were frequently included in the reports of that period of American diplomats serving in Turkey. In this study, how the developments of the Journalist Cases seen in the Independence Tribunals reflected in the reports of the American diplomats will be examined. In general, the diplomats' approach to the Journalists Cases is judgmental. Although the diplomats stated the legal dimension of these cases, they evaluated and interpreted them as political cases on the grounds that there was not enough evidence. Moreover, along with The U.S. National Archives (NARA), the related news in the newspapers of that era, the memories of the journalists and the members of the Independence Tribunals, and the relevant literature will also be referred.

İstiklâl Savaşı‟nın kazanılmasından sonra saltanatın kaldırılıp halifeliğin bir süre daha geride bırakılması, Meclis‟in kendisini feshetmesi, seçimlerin yenilenmesi, Halk Fırkası‟nın kurulması, Cumhuriyetin ilanı gibi kısa bir sürede vuku bulan gelişmeler İstanbul basının tepkisine neden olmuştur. Bu gelişmeler İstanbul‟da bir İstiklâl Mahkemesi‟nin kurulmasına yol açmıştır. 4 Mart 1925‟te Meclis kararıyla Şeyh Said İsyanı‟nı bastırmak üzere Şark İstiklâl Mahkemesi kurulmuştur. Bu mahkemedeki yargılama sürecinde Şeyh Said, bazı gazete yayınlarının kendilerini isyana sürüklediği ve hükümete karşı cephe almalarında etken olduğunu iddia etmiştir. Gazeteciler Davası olarak bilinen yargılamalar ve konuyla ilgili gelişmeler, Türkiye‟de görev yapan dönemin Amerikan diplomatlarının raporlarında da sıklıkla yer almıştır. Bu çalışmada İstiklâl Mahkemeleri‟nde görülen Gazeciler Davasının Amerikan diplomatlarının raporlarına nasıl yansıdığı incelenecektir. Genel olarak, diplomatların Gazeteciler Davasına yaklaşımı eleştireldir. Diplomatlar bu davaların hukuki yönünün olduğunu belirtmelerine rağmen yeterli delil olmadığı gerekçesiyle davaları, siyasi davalar olarak değerlendirmiş ve yorumlamışlardır. Amerikan Milli Arşivi‟nin yanı sıra, dönemin gazetelerinde yer alan ilgili haberlere ve yargılanan gazeteciler ile yargılamayı yapan İstiklâl Mahkemesi üyelerinin hatıralarına ve konuyla ilgili literatüre de başvurulacaktır.
Amerikan diplomatlarının raporlarına göre İstanbul ve şark İstiklâl mahkemesinde gazeteciler davası
Keywords: Atatürk Era; Independence Tribunals; Mark L. Bristol; Jefferson Patterson; Sheldon Leavitt Crosby; Atatürk Dönemi; İstiklâl Mahkemeleri